Pengaruh Transfer Pricing, Intensitas Aset, dan Profitabilitas Terhadap Penghindaran Pajak - Ramadzani, Sania Wihelwina Iga; Durya, Ngurah Pandji Mertha Agung; Prajanto, Agung (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the effect of transfer pricing, asset intencity, and profitability on tax avoidance in companies in the energy sector. This study included in the category of associative quantitative research through purposive sampling in obtaining a sample of 89 companies. All companies listed on the Indonesian Stock Exchange (IDX) in the period 2019-2023 are target population of the study. The data collection technique is through documentation studies, means data that has go public or published through the official IDX website. The type of data analysis is through multiple linear regression with the help of the SPSS 26.0 Data Processing Application. The research indicates that transfer pricing and asset intencity have negative impacts on tax avoidance, while profitability has no impact on tax avoidance. This study is a replication study with the difference are on the selection of the company sector and the research period. The study emphasizes the importance of tax policy supervision and the implementation of stricter regulation to minimize tax avoidance practices that can reduce state revenue.